2012
DOI: 10.1097/mpa.0b013e31824bd89f
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation in Acute Pancreatitis

Abstract: These results may indicate an important role of platelet activation in the pathogenesis of acute pancreatitis and the development of complications in S-AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…As there was no statistical difference in the amount of platelet counts between patients with and without intra‐abdominal infection, platelet functions, including their capacity of adhesion, aggregation, deformation and release, may be the predictive factors with greater relevance to intra‐abdominal infection, which coincides with the results of previous studies demonstrating that platelet function was altered during AP . An elevated MA indicated a hypercoagulation state in patients with intra‐abdominal infection, which is in accordance with the idea that enhanced platelet activation and a hypercoagulation state could be present in the late phase of SAP . Most of the predictive factors were coagulation parameters.…”
Section: Discussionsupporting
confidence: 87%
“…As there was no statistical difference in the amount of platelet counts between patients with and without intra‐abdominal infection, platelet functions, including their capacity of adhesion, aggregation, deformation and release, may be the predictive factors with greater relevance to intra‐abdominal infection, which coincides with the results of previous studies demonstrating that platelet function was altered during AP . An elevated MA indicated a hypercoagulation state in patients with intra‐abdominal infection, which is in accordance with the idea that enhanced platelet activation and a hypercoagulation state could be present in the late phase of SAP . Most of the predictive factors were coagulation parameters.…”
Section: Discussionsupporting
confidence: 87%
“…There is a stimulation of megakaryopoiesis in the early stages of the in ammatory process associated with hyperlipidemia-induced SAP, which produces a large amount of young and large platelets with high procoagulation potential [23]. Osada et al [6] observed a signi cant increase in the number of large platelets in the AP groups; the median and mean MPV remained at high levels during the acute phase in the mild and severe AP groups. Moreover, the MPV levels showed a downward trend in remission phase in patients with SAP, which supported our results.…”
Section: Discussionmentioning
confidence: 99%
“…There is a stimulation of megakaryopoiesis in the early stages of the inflammatory process associated with hyperlipidemia-induced SAP, which produces a large amount of young and large platelets with high procoagulation potential [23]. Osada et al [6] observed a significant increase in the number of large platelets in the AP groups; the median and mean MPV remained at high levels during the acute phase in the mild and severe AP groups. Moreover, the MPV levels showed a downward trend in remission phase in patients with SAP, which supported our results.…”
Section: Discussionmentioning
confidence: 99%